Adrenal Function in Hypothyroidism. Issue 5692 (7th February 1970) - Havard, C. W. H.; Saldanha, V. F.; Bird, R.; Gardner, R.
Abstract : In ten patients with hypothyroidism the adrenal response to stimulation with tetracosactrin was found to be normal, and to be unchanged after they had been treated with thyroxine. Though the response to insulin hypoglycaemia was less in the hypothyroid phase, it was never outside the normal limits. Hence it seems unlikely that the adrenal response to stress is appreciably lowered in hypothyroidism.